FAKTOR PENDORONG DAN PENARIK PERDAGANGAN ORANG (HUMAN TRAFFICKING) DI SUMATERA BARAT - Sylvia, Ike (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2014)
This study is intended to reveal: (1) the description of the real conditions and the information and facts about human trafficking in West Sumatra, (2) the â€œpush and pull factorsâ€ of human trafficking. This study uses a mixed method using secondary and primary data. Primary data is collected through questionnaires, interviews and focus group discussions in accordance with the purpose of research. Secondary data is collected by observing the documents available at the village, district, regency, provincial, and national levels as well as other relevant agencies and literature review. The results show that the push factors of human trafficking in West Sumatra are; (1) the unavailability of the desired jobs in the country (2) early marriage, with a high risk of divorce, domestic violence, poverty, etc, (3) requirements that must be met before applying, (4) Poverty (5) low formal education, so easily provoked by news, (6) Administration of birth registration is not good, (7) Lack of social control. Meanwhile the pull factors of human trafficking are (1) the temptation to make a living outside the hometown, (2) Information that life is better and successful outside hometown, (3) better salary outside hometown, (4) simple procedures conducted by labor brokers who trap women in human trafficking. The community leaders, religious leaders, as well as â€˜bundo kanduangâ€™, â€˜ninik mamakâ€™ are expected to play the role as agents of inheriting unwritten values, norms and traditions to the nephews and children within the family, so they will be guided in their lives and not trapped by the human trafficking brokers seduction. Keywords: human trafficking, push and pull factors